The Bond Market Structure In Malaysia And Its Liquidity - Lone, Tham Kok (2002)
Bonds are a type of debt instruments issued with a defined life and final maturity and investors are paid an agreed income. Upon maturity, the issuer returns the agreed principal sum of money to the investor. The basic characteristics of a bond are namely, a maturity date, a fixed rate of interest payment or coupon or a fixed face or par value ( principal sum) redeemed upon maturity. In Malaysia, the bonds are issued as either conventional bonds or islamic bonds.